2020
DOI: 10.1002/brb3.1539
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes, and practices with respect to epilepsy among primary and secondary school teachers in the city of Niamey, Niger

Abstract: Objective We aimed firstly to evaluate knowledge, attitudes, and practices about epilepsy among primary and secondary school teachers in the city of Niamey and secondly to formulate targeted sensitization messages for these teachers. Materials and methods A descriptive cross‐sectional survey was carried out among primary and secondary school teachers in the city of Niamey, capital of Niger, using a self‐administered questionnaire including questions related to knowledge, attitudes, and practices about epilepsy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 11 publications
1
23
0
Order By: Relevance
“…In the present survey, 41.9% of the respondents considered epilepsy as a contagious disease. These findings are similar to those reported in the surveys conducted in Niamey, 7 and Sakoira 9 in 46.2% and 42%, respectively. Findings lower than ours were reported in an Egyptian study at 1.6%, 3 and an Ethiopian study at 1%.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the present survey, 41.9% of the respondents considered epilepsy as a contagious disease. These findings are similar to those reported in the surveys conducted in Niamey, 7 and Sakoira 9 in 46.2% and 42%, respectively. Findings lower than ours were reported in an Egyptian study at 1.6%, 3 and an Ethiopian study at 1%.…”
Section: Discussionsupporting
confidence: 91%
“…5 Negative attitudes towards SCWE come from both their school peers and their school teachers due to their erroneous cultural and religious beliefs about epilepsy such as an incurable and contagious disease. 2,6,7 As reported previously, reducing the social stigma and discrimination associated with epilepsy can help to improve the quality of life of children with epilepsy. 8 Thus, to reduce the social stigma and discrimination associated with epilepsy, it is necessary to study the general knowledge about epilepsy of the actors of the school environment to identify the factors favoring the social stigma and discrimination towards SCWE.…”
Section: Introductionmentioning
confidence: 88%
“…However, Ibinga et al reported that 42.8% of the staff in their survey thought that epilepsy could be treated by modern or traditional medicine [15]. In this survey, 17% of the staff in this survey thought that epilepsy is an infectious disease, however, a survey in Niger, epilepsy is considered to be a contagious disease by 46.2% of respondents [19]. This misconception among school teachers has an impact on teachers' attitudes towards children with epilepsy, negative attitudes and beliefs about epilepsy of the school teachers can lead to the expulsion of the child and even the no schooling.…”
Section: Discussionmentioning
confidence: 61%
“…This misconception among school teachers has an impact on teachers' attitudes towards children with epilepsy, negative attitudes and beliefs about epilepsy of the school teachers can lead to the expulsion of the child and even the no schooling. Besides, some children with epilepsy may be rejected from their peers for fear of being contaminated [19]. The results of this survey indicate that the overall knowledge of staff members about epilepsy is lacking, as evidenced by the low but visible frequency of incorrect responses about how to work with children with epilepsy.…”
Section: Discussionmentioning
confidence: 93%
“…Details of the design and protocol have been reported previously. 2 In brief, we conducted a descriptive crosssectional survey among nurses in the city of Niamey, Niger between June and July 2019 to evaluate their knowledge about epilepsy. There are two categories of nurses in Niger:…”
Section: Study Design and Participantsmentioning
confidence: 99%